Pengembangan Keterampilan Guru Dalam Membuat Buku Terbitan Di SMK Al-Ittihad Cianjur - Mentari Anugrah Imsa; Menati Fajar Rizky; Firdaus Hadi Santosa (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
Efforts have been made to educate the nation's life, one of which is a policy for teachers as the main party who contributes greatly to education. As an educator, a teacher needs to create a meaningful educational atmosphere and be professionally committed and set an example. One thing that can be done is to have textbooks to support the quality of education. However, from an analysis of the situation at one of the Al-Ittihad Cianjur Vocational Schools, the majority of teachers have never published a book to use for the teaching and learning process. The results of interviews and pre-activity observations also showed that there had never been any training that provided material for publishing textbooks. On the other hand, some teachers already have modules that can be turned into published books. Therefore, this service seeks to improve the abilities and understanding of teachers at Al-Ittihad Cianjur Vocational School in creating published books that can be used for the teaching and learning process. The material was provided through socialization and attended by 15 teachers from various expertise. Based on the results of interviews after the activity, teachers have knowledge about the flow of book publishing and also the process of changing modules into textbooks. However, I will still think more about making books because there are too many activities to do at school.